2011
DOI: 10.1074/jbc.m110.165548
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Muscle A-type Lamin-interacting Protein (MLIP)

Abstract: Mutations in the A-type lamin (LMNA) gene are associated with age-associated degenerative disorders of mesenchymal tissues, such as dilated cardiomyopathy, Emery-Dreifuss muscular dystrophy, and limb-girdle muscular dystrophy. The molecular mechanisms that connect mutations in LMNA with different human diseases are poorly understood. Here, we report the identification of a Muscle-enriched A-type Lamin-interacting Protein, MLIP (C6orf142 and 2310046A06rik), a unique single copy gene that is an innovation of amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 51 publications
6
54
0
Order By: Relevance
“…Because SLC39A8 encodes a zinc transporter [17], its association with DCM may also be related to the cardioprotective role of zinc [18]. In the nuclear envelope, MLIP (also known as CIP) directly interacts with the N-terminal region of lamin (LMNA) [19]. Dominant mutations in LMNA cause DCM and other hereditary multisystemic diseases and several pathogenic mutations of LMNA are located in its MLIP interacting domain [20].…”
Section: Discussionmentioning
confidence: 99%
“…Because SLC39A8 encodes a zinc transporter [17], its association with DCM may also be related to the cardioprotective role of zinc [18]. In the nuclear envelope, MLIP (also known as CIP) directly interacts with the N-terminal region of lamin (LMNA) [19]. Dominant mutations in LMNA cause DCM and other hereditary multisystemic diseases and several pathogenic mutations of LMNA are located in its MLIP interacting domain [20].…”
Section: Discussionmentioning
confidence: 99%
“…1C). We previously reported that MLIP was found in the nucleus, interacting with A-type lamin, and in the cytoplasm of mouse C2C12 myoblasts (3). Using the Mlip Ϫ/Ϫ heart as negative control, we further characterized the localization of MLIP in the adult Mlip ϩ/ϩ heart by immunostaining.…”
Section: Mlip Is Not Required For Normal Cardiac Development Andmentioning
confidence: 99%
“…Because MLIP is highly expressed in the heart, where its isoform expression pattern is complex (Ref. 3 and Fig. 1C), we hypothesized that MLIP would have specific functions in myocardial physiology.…”
Section: Detailed Phenotypic Analysis Of the Mlipmentioning
confidence: 99%
See 2 more Smart Citations